Smile to Heal: Entertainment and humanization to hospitalized children - Felicio, Vanusa; Costa Valbão Freire, Sigrid; Villefort dos Santos Borges, Fabrícia; Moraes, Rodrigo; Pratte Santos, Rodrigo (Guará Journal, 2017)
The Project Smile to Heal started as academic extension project to be developed with hospitalized children in the Grande Vitoria region, Espirito Santo, Brazil. During the events, were organized games, artistic attractions, theaters and other activities that aim to interaction between health professionals, volunteers and patients. The entertainment was used to liven the hospitalized children, since the isolation impossible the leisure time. Could smile makes the child is biologically stimulated to trigger reactions that positively affect their recovery. Several countries have adopted the method of "healing the smile", and studies show that entertainment helps in the treatment of patients, especially children. After performing the events with the hospitalized children, it can be observed that the hospital has become a more pleasant space for child care. Forms of artistic expression facilitated communication, enabling better acceptance of therapy by patients and reducing pain and anxiety of families. Finally, the smiles promoted by the team of "Smile to Heal" allowed a complementary modality of aid in the treatment of hospitalized pediatric patients.